Fundamentals of cognitive neuroscience a beginner's guide - Gage, Nicole M.; Baars, Bernard (Academic Press is an imprint of Elsevier, 2018)
Fundamentals of Cognitive Neuroscience: A Beginner's Guide, Second Edition, is a comprehensive, yet accessible, beginneru2019s guide on cognitive neuroscience. This text takes a distinctive, commonsense approach to help newcomers easily learn the basics of how the brain functions when we learn, act, feel, speak and socialize. This updated edition includes contents and features that are both academically rigorous and engaging, including a step-by-step introduction to the visible brain, colorful brain illustrations, and new chapters on emerging topics in cognition research, including emotion, sleep and disorders of consciousness, and discussions of novel findings that highlight cognitive neuroscienceu2019s practical applications. Written by two leading experts in the field and thoroughly updated, this book remains an indispensable introduction to the study of cognition.--